Predicting risk of atrial fibrillation after heart valve surgery: evaluation of a Brazilian risk score Predizendo risco de fibrilação atrial após cirurgia cardíaca valvar: avaliação de escore de risco brasileiro - Michel Pompeu Barros de Oliveira Sá; Marcus Villander Barros de Oliveira Sá; Ana Carla Lopes de Albuquerque; Belisa Barreto Gomes da Silva; José Williams Muniz de Siqueira; Phabllo Rodrigo Santos de Brito; Paulo Ernando Ferraz; Ricardo de Carvalho Lima (Brazilian Journal of Cardiovascular Surgery, 2012)
OBJECTIVE: The aim of this study is to evaluate the applicability of a Brazilian score for predicting atrial fibrillation (AF) in patients undergoing heart valve surgery in the Division of Cardiovascular Surgery of Pronto Socorro Cardiológico de Pernambuco - PROCAPE (Recife, PE, Brazil). METHODS: Retrospective study involving 491 consecutive patients operated between May/2007 and December/2010. The registers contained all the information used to calculate the score. The outcome of interest was AF. We calculated association of model factors with AF (univariate analysis and multivariate logistic regression analysis), and association of risk score classes with AF. RESULTS: The incidence of AF was 31.2%. In multivariate analysis, the four variables of the score were predictors of postoperative AF: age >70 years (OR 6.82; 95%CI 3.34-14.10; P<0.001), mitral valve disease (OR 3.18; 95%CI 1.83-5.20; P<0.001), no use of beta-blocker or discontinuation of its use in the postoperative period (OR 1.63; 95%CI 1.05-2.51; P=0.028), total fluid balance > 1500 ml at first 24 hours (OR 1.92; 95%CI 1.28-2.88; P=0.002). We observed that the higher the risk class of the patient (low, medium, high, very high), the greater is the incidence of postoperative AF (4.2%; 18.1%; 30.8%; 49.2%), showing that the model seems to be a good predictor of risk of postoperative AF, in a statistically significant association (P<0.001). CONCLUSIONS: The Brazilian score proved to be a simple and objective index, revealing a satisfactory predictor of development of postoperative AF in patients undergoing heart valve surgery at our institution. OBJETIVO: O objetivo deste estudo é avaliar a aplicabilidade de um escore brasileiro na predição de fibrilação atrial (FA) pós-operatória em pacientes submetidos à cirurgia cardíaca valvar na Divisão de Cirurgia Cardiovascular do Pronto Socorro Cardiológico de Pernambuco - PROCAPE (Recife, PE, Brasil). MÉTODOS: Estudo retrospectivo envolvendo 491 pacientes consecutivos operados entre maio/2007 e dezembro/2010. Os registros continham todas as informações utilizadas para calcular a pontuação. O desfecho de interesse foi FA. Calculamos associação de fatores do escore com FA (análise univariada e análise de regressão logística multivariada), e associação de classes de risco do escore com FA. RESULTADOS: A incidência de FA foi de 31,2%. Na análise multivariada, as quatro variáveis do escore foram preditores de FA pós-operatória: idade> 70 anos (OR 6,82; IC95% 3,34-14,10; P<0,001), doença valvular mitral (OR 3,18; IC95% 1,83-5,20; P<0,001), sem uso de beta-bloqueador ou interrupção de seu uso no pós-operatório (OR 1,63; IC95% 1,05-2,51; P=0,028), balanço hídrico total >1500 ml nas primeiras 24 horas (OR 1,92; IC95% 1,28-2,88; P=0,002). Observamos que, quanto maior a classe de risco do paciente (baixa, média, alta, muito alta), maior é a incidência de FA pós-operatória (4,2%; 18,1%; 30,8%; 49,2%), mostrando que o modelo parece ser um bom preditor de risco de FA pósoperatória, em uma associação estatisticamente significativa (P<0,001). CONCLUSÕES: O escore brasileiro revelou-se um índice simples e objetivo, revelando-se um preditor satisfatório de desenvolvimento de FA pós-operatória em pacientes submetidos à cirurgia cardíaca valvar em nossa instituição.